Cognitive and institutional perspectives of eco effiency: A new research landscape towards factor four (or more) - Raimund Bleischwitz (Wuppertal Institut für Klima, Umwelt, Energie, 2002)
The paper sketches out a theoretical framework for analysing the interplaybetween eco-efficiency, cognition and institutions. It derives from analyticalshortfalls of the prevailing literature, which features strongly engineering andbusiness economics, by using insights from New Institutional Economics, fromCognitive Sciences and, partly, from Evolutionary Economics. It emphasises therole cognition and institutions play in the adoption of green technologies byfirms. A cognitive perspective derives from recent research on simple heuristicsand context-based rationality; it is proposed that those recent findings can serve toanalyse decision-making of individual actors or firms and, thus, should complement economic analysis. A second proposition is that eco-efficiency and normative rules such as a Factor Four strongly rely upon institutions, i.e. theability of institutions to evolve over time and the development of those institutionsthat are most appropriate to enhance technological change. In this regard, businessinstitutions and competition are crucial, but regulatory needs remain in order tosafeguard continuity of knowledge creation. The framework allows for an analysiswhy overall adoption of eco-efficiency still can be considered relatively slow andwhy some markets and firms are far ahead. As a brief case study the articlereflects upon German waste law's ability to enhance eco-efficiency.
urn:nbn:de:bsz:wup4-opus-14172
Keywords: D8; L1; O3; Q2; 330; Technical Change; Institutional Change; Cognition; Knowledge Creation; Environmental Management; Factor Four; Nachhaltige Entwicklung; Umwelttechnik; Technischer Fortschritt; Umweltbewusstsein; Institutioneller Wandel; Deutschland; Kognition